Continuidades e descontinuidades em representações do leitor infantil: uma análise de projeções discursivas do leitor da Folhinha de 1963 aos dias atuais - Baldin, Ana Luiza Menezes (2016)
Summary: In this paper, we analyze some writing practices adopted by Folhinha supplement linked to the newspaper Folha de S. Paulo since its launch, on September 8th, 1963, to the present day, seeking to raise certain representations of their children's readers, entered and manifested in the published texts (analyzing its themes, its formal composition on the page, its articulation with images, their lexical and syntactic selection etc. ). For this survey and analysis of discursive representations of the reader, we mobilize the theoretical and methodological assumptions of the French guidance Discourse Analysis, as well as some principles developed by the Cultural History of Reading. Considering that the publication has children as target audience and the fact that has been published since its creation regularly with weekly publication, the corpus selection was the choice of examples concerning the theme "Children's day", so that we could select the publications that made direct reference or indirectly to that date, celebrated in Brazil on October 12th and present throughout all these years supplement the publication. In our analysis of the corpus, we seek to trace the continuities and discontinuities adopted as the writing techniques and on the selection and approach to issues, in order to identify any traces about the profile of this Bantam player. Among the writing strategies that are analyzed forms of subjective projection and simulation of dialogue with readers and thematic orientation of some specimens with a view to building a patriotic reader, the nation's symbol of the future, and consumers.